Role of transient receptor potential ion channels and evoked levels of neuropeptides in a formaldehyde-induced model of asthma in BALB/c mice. - Yang Wu (Public Library of Science (PLoS), 2013)
Objective Asthma is a complex pulmonary inflammatory disease characterized by the hyper-responsiveness, remodeling and inflammation of airways. Formaldehyde is a common indoor air pollutant that can cause asthma in people experiencing long-term exposure. The irritant effect and adjuvant effect are the two possible pathways of formaldehyde promoted asthma. Methodology/principal findings To explore the neural mechanisms and adjuvant effect of formaldehyde, 48 Balb/c mice in six experimental groups were exposed to (a) vehicle control; (b) ovalbumin; (c) formaldehyde (3.0 mg/m(3)); (d) ovalbumin+formaldehyde (3.0 mg/m(3)); (e) ovalbumin+formaldehyde (3.0 mg/m(3))+HC-030031 (transient receptor potential ankyrin 1 antagonist); (f) ovalbumin+formaldehyde (3.0 mg/m(3))+ capsazepine (transient receptor potential vanilloid 1 antagonist). Experiments were conducted after 4 weeks of combined exposure and 1-week challenge with aerosolized ovalbumin. Airway hyper-responsiveness, pulmonary tissue damage, eosinophil infiltration, and increased levels of interleukin-4, interleukin-6, interleukin-1β, immunoglobulin E, substance P and calcitonin gene-related peptide in lung tissues were found in the ovalbumin+formaldehyde (3.0 mg/m(3)) group compared with the values seen in ovalbumin -only immunized mice. Except for interleukin-1β levels, other changes in the levels of biomarker could be inhibited by HC-030031 and capsazepine. Conclusions/significance Formaldehyde might be a key risk factor for the rise in asthma cases. Transient receptor potential ion channels and neuropeptides have important roles in formaldehyde promoted-asthma.